An Energy-Efficient ADO-OFDM System for Optical Wireless Communication - Wei-Wen Hu (IEEE Photonics Journal, 2023)
This paper proposes an energy-efficient asymmetrically clipped direct-current (DC) biased optical orthogonal frequency division multiplexing (EEADO-OFDM) scheme, which replaces the fixed DC bias of DC biased optical OFDM (DCO-OFDM) branch with a adaptive DC bias for optical wireless communications. In the EEADO-OFDM, an adaptive DC bias is dynamically designed according to amplitude of DCO-OFDM signal samples to enhance the power efficiency. After superimposing the obtained DC bias on the original DCO-OFDM signal, the resultant DCO-OFDM signal is non-negative and further ensure that a non-negative EEADO-OFDM signal is produced by directly combining DCO-OFDM signal with the clipped asymmetrically clipped optical OFDM (ACO-OFDM) signal. In particular, the interference caused by the obtained DC bias is proved to fall on even subcarriers only, which implies that the interference can be modulated on the partial odd subcarriers of ACO-OFDM branch. Afterward, we could use conventional ACO-OFDM receiver to demodulate the adopted odd subcarriers for the detection of interference. Simulation results show that, under the equal optical power constraints, the proposed EEADO-OFDM achieves no error floors of bit error rate compared with the ADO-OFDM, thus indicating that the clipping noise is always negligible in EEADO-OFDM.